Fish mucus mediated biosynthesis of copper oxide nanoparticles: spectral characterization, morphology and biological activity. (22nd December 2020) - Chinnadurai, G; Subramanian, R; Ahamed, Maqusood
Abstract: Simple methodology was developed to synthesize copper oxide nanoparticles (CuO NPs) using mucus of Channa striatus ( C. striatus ). The mucus of C. striatus is known for its biological properties due to the presence of numerous amino acids. This mucus was used as stabilizing agent for CuO NPs synthesis from copper acetate. The prepared CuO NPs were characterized by fourier transforms infrared spectrometer (FTIR), powder x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM), energy dispersive x-ray analysis (EDX) and transmission electron microscope (TEM) coupled with selected area diffraction pattern (SAED). The FTIR study suggested the utilization of mucus in the synthesis of CuO NPs. The XRD data also confirmed formation of pure crystalline phase of CuO NPs. Fish mucus stabilized CuO NPs exhibited significant activity against HeLa cells. The results of cell death clearly indicated that the synthesized CuO nanoparticles could be served as a biomaterial for anticancer treatment.